Toward Understanding Polar Heat Transport Enhancement in Subglacial Oceans on Icy Moons - Hartmann, Robert; Stevens, Richard J. A. M.; Lohse, Detlef; Verzicco, Roberto (Geophysical research letters, 2024)
The interior oceans of several icy moons are considered as affected by rotation. Observations suggest a larger heat transport around the poles than at the equator. Rotating Rayleigh‐Bénard convection (RRBC) in planar configuration can show an enhanced heat transport compared to the non‐rotating case within this “rotation‐affected” regime. We investigate the potential for such a (polar) heat transport enhancement in these subglacial oceans by direct numerical simulations of RRBC in spherical geometry for Ra = 106 and 0.7 ≤ Pr ≤ 4.38. We find an enhancement up to 28% in the “polar tangent cylinder,” which is globally compensated by a reduced heat transport at low latitudes. As a result, the polar heat transport can exceed the equatorial by up to 50%. The enhancement is mostly insensitive to different radial gravity profiles, but decreases for thinner shells. In general, polar heat transport and its enhancement in spherical RRBC follow the same principles as in planar RRBC. Plain Language Summary The icy moons of Jupiter and Saturn like for example, Europa, Titan, or Enceladus are believed to have a water ocean beneath their ice crust. Several of them show phenomena in their polar regions like active geysers or a thinner crust than at the equator, all of which might be related to a larger heat transport around the poles from the underlying ocean. We simulate the flow dynamics and currents in these subglacial ocean by high‐fidelity simulations, though still at less extreme parameters than in reality, to study the heat transport and provide a possible explanation of such a “polar heat transport enhancement.” We find that the heat transport around the poles can be up to 50% larger than around the equator, and that the believed properties of the icy moons and their oceans would allow polar heat transport enhancement. Therefore, our results may help to improve the understanding of ocean currents and latitudinal variations in the oceanic heat transport and crustal thickness on icy moons. Key Points The polar heat transport in spherical rotating Rayleigh‐Bénard convection experiences an enhancement by rotation The influence of rotation differs at low latitudes: the heat flux is reduced and compensates the polar enhancement on the global average In combination, this strengthens the latitudinal variation between polar and equatorial heat flux for Prandtl numbers larger than unity